Standardized transbronchial needle aspiration procedure for intrathoracic lymph node staging of non-small cell lung cancer - Jin, Xu-Ru (J Thorac Dis, 2015)
BACKGROUND: Thoracic lymph node (LN) metastasis is the determining factor for NSCLC staging. However, enlargement in thoracic LNs, which can be detected by chest computed tomography (CT), may not be adequate for NSCLC staging. This study aimed to investigate the effectiveness of a new transbronchial needle aspiration (TBNA) procedure to improve the sensitivity and accuracy of lung cancer diagnosis and staging. METHODS: A standardized TBNA procedure was performed on enlarged and non-enlarged LNs in the order of N3 to N1 station according to Wang’s LN map. The status of LN metastasis determined by the standardized TBNA procedure was compared with the results from CT scan. RESULTS: The TBNA biopsy revealed that 21.43% of non-enlarged LNs were malignant. Compared with chest CT, the standardized TBNA procedure improved the accuracy of LN metastasis staging and discovered skip LN metastasis. CONCLUSIONS: The standardized TBNA procedure of this study may be recommended to be used as a routine TBNA procedure, in which LNs should be biopsied in the order of N3 to N1 station and both enlarged and non-enlarged LNs should be included to improve the accuracy of lung cancer staging.